Programmable morphing, electroactive porous shape memory polymer composites with battery-voltage Joule heating stimulated recovery - Lai-Iskandar, S. (2022)
Direct fabrication of electroactive shape memory polymer composites (eSMPCs) into complex non-planar geometries is highly desirable to enable remotely deployable, form-functional structures. However, traditional processes such as injection molding, casting, and extrusion limit the producible geometries to planar ribbons, wires, or tubes and the design of deployment modes to flattening-out/self-folding motions. To achieve low-voltage eSMPCs with a complex geometry, we report a direct fabrication strategy of bespoked-geometry eSMPCs via a two-stage sequential cure-and-foam technique for a new type of porous eSMPC, functionalized with 3D graphene nanofoam monolith (3DC). In our method, we resolved the difficulty in shaping fragile 3DC, and thus, various complex shape transforms (curved, helical, and wavy) can be intuitively designed via direct sculpting. Our method can be compatible with kirigami techniques for the design of hierarchical and combinatorial shape-change structures. 3DC not only serves as an intrinsic heater but, during synthesis, its cell walls also act as a confinement framework for architecting porosity within 3DC-eSMPCs, which can be actuated with low-voltage (7.5 V, <2 W). The herein reported 3DC-eSMPC and its synthesis strategy represent a new method and material to fabricate low-voltage deployables of bespoked shapes, capable of low-voltage actuation.